The History of Pathologists' Assistants: A Tale of 2 Educational Mavericks...Thomas D.Kinney - Wright Jr, James R. (Archives of Pathology & Laboratory Medicine, 2019)
Context.--The use of medical technologists to assist with clinical pathology workload has been common since the 1930s. In stark contrast, most aspects of anatomical pathology have traditionally been considered to be medical work that must be performed by pathologists or residents. Objective.--To describe the history of the pathologists' assistant profession in North America. Design.--Available primary and secondary historical sources were reviewed. Results.--The concept of physician assistants, capable of performing delegated medical tasks, was created by Eugene A. Stead Jr, MD, at Duke University in 1965. When this profession began, it was quickly embraced by the American Medical Association, which took ownership related to certification and licensing of practitioners as well as external accreditation of training programs. Because of concerns about pathology manpower in the late 1960s, Thomas D. Kinney, MD, also at Duke University, developed the first training program for pathologists' assistants in 1969. Pathologists' assistants were not immediately accepted by many academic pathologists, especially related to work in the surgical pathology gross room. Organized pathology did not help the new profession develop standards, and so in 1972 pathologists' assistants created their own professional organization, the American Association of Pathologists' Assistants. Although it took several decades, the association was eventually able to forge relationships with the National Accrediting Agency for Clinical Laboratory Sciences for training program accreditation and the American Society for Clinical Pathology for board certification for practitioners. The development of the profession in Canada is also described. Conclusions.--The pathologists' assistant profession is now well established in North America.